Does wage dispersion make all firms productive? - Benoît Mahy; Francois Rycx; Mélanie Volral (Institute for the Study of Labor (IZA), 2011)
This article puts the relationship between wage dispersion and firm productivity to an updated test, taking advantage of access to detailed Belgian linked employer-employee panel data. Controlling for simultaneity issues, time-invariant workplace characteristics and dynamics in the adjustment process of productivity, empirical results reveal the existence of a positive impact from conditional intra-firm wage dispersion to firm productivity (measured by the average value added per hour worked), which however decreases for higher dispersion levels. Findings thus suggest that the incentive effect of wage dispersion, predicted for instance by the tournament model, dominates fairness and/or sabotage considerations. Further results reveal that the influence of wage dispersion on firm productivity is stronger among firms with a larger proportion of highly skilled workers but does not depend on whether wages are collectively renegotiated at the firm level.
urn:nbn:de:101:1-201106224726
Keywords: J31; J24; M5; 330; wage dispersion; labour productivity; personnel economics; matched employer-employee panel data